The Effect of Wage Amounts and Certification on Teacher Performance in HKBP Pagar Jati Private Elementary School Lubuk Pakam District - Lisna Maya Sari Sihaloho (Institute of Computer Science (IOCS), 2018)
This study aims to determine the Effect of Wage Amounts and Certification on the Performance of HKBP Pagar Jati Private Elementary School Teachers in Lubuk Pakam District and to find out the dominant variables on teacher performance. The samples used in this study were all HKBP Private Elementary School Teachers in teak fences, Lubuk Pakam District. The number of samples is calculated using the formula according to Sugyono (2016), so we get a total sample of 17 people. The results of this study indicate that the independent variable is the wage magnitude factor (X1), Certification (X2), a positive and significant effect on teacher performance. The results of this study also showed that the dominant variable influencing teacher performance at the HKBP Pagar Jati elementary school was Certification (X2).